Comparison of Pulmonary Outcome in Minimally Invasive (TCRAT) and Full Sternotomy CABG - Sellin, Christian; Sand, Ulrike; Demianenko, Volodymyr; Schmitt, Christoph; Schäfer, Benedikt; Schier, Robert; Doerge, Hilmar (The Thoracic and Cardiovascular Surgeon, 2024)
Background Pulmonary complications are among the main causes of increased mortality, and morbidity, as well as prolonged intensive care unit (ICU) and hospital stay after cardiac surgery. Recently, a sternum-sparing concept of minimally invasive total coronary revascularization via anterior minithoracotomy (TCRAT) was introduced. A higher risk of pulmonary injury could be anticipated due to the thoracic incision and the longer duration of surgery. Pulmonary complications in TCRAT were compared to standard coronary artery bypass grafting (CABG) via full median sternotomy (FS).Methods Records of 151 consecutive TCRAT (from September 2021 to November 2022) and 229 consecutive FS patients (from January 2017 to December 2018) patients, who underwent elective or urgent CABG, were analyzed. Preoperative baseline characteristics (age, sex, body mass index, diabetes, hypertension, chronic obstructive pulmonary disease, smoking status, left ventricular ejection fraction, pulmonary hypertonus, and EuroScore II) were comparable between groups.Results Differences between examined groups examined were found for the pulmonary parameters: Horowitz index 6 hours after operation (TCRAT 270 ± 72 vs. FS 293 ± 73, p < 0.05), pneumothorax (TCRAT 0% vs. FS 2.6%, p < 0.05), bronchoscopies (TCRAT 5.9% vs. FS 1.7%, p < 0.05), and pleural effusion (TCRAT 8.6% vs. FS 3.5%, p < 0.05). Moreover, there were differences between groups with regard to mean ICU stay (TCRAT 2.4 ± 3.0 days vs. FS 1.8 ± 1.8 days, p < 0.05), stroke (TCRAT 0% vs. FS 1.3%, p < 0.05), and hospital stay (TCRAT 10.9 ± 8.5 days vs. FS 13.2 ± 9.3 days, p < 0.05). There were no differences regarding atelectasis, reintubations, tracheostomies, ventilation time, and mortality.Conclusion Pulmonary complications in terms of pleural effusions were more common with TCRAT, however, without substantial impact on clinical outcome.
Keywords: minimally invasive cardiac surgery; CABG; TCRAT; pulmonary complications; outcomes